Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1016/j.cardiores.2006.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Composite polymorphisms in the ryanodine receptor 2 gene associated with arrhythmogenic right ventricular cardiomyopathy

Abstract: The RyR2 channel leak under diastolic conditions could cause SR-Ca2+ depletion, concomitantly arrhythmogenesis and heart failure in a subgroup of ARVC patients of genotype T4. A change in the RyR2 subunit composition due to the combined expression of both SNPs alters the behaviour of the tetrameric channel complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 30 publications
5
55
0
Order By: Relevance
“…Here, we successfully predicted that the K897T nsSNP creates a potential phosphorylation site, which might be phosphorylated by a variety of PKs, including AGC/AKT (Table III). Also, it was proposed that a G1886S nsSNP of RYR2 (NM_001035) might generate a protein kinase C phosphorylation site (44). And our prediction result was consistent with the previous study (Table III) (44).…”
Section: Genome-wide Identification Of Potential Phossnps In Hu-supporting
confidence: 82%
See 1 more Smart Citation
“…Here, we successfully predicted that the K897T nsSNP creates a potential phosphorylation site, which might be phosphorylated by a variety of PKs, including AGC/AKT (Table III). Also, it was proposed that a G1886S nsSNP of RYR2 (NM_001035) might generate a protein kinase C phosphorylation site (44). And our prediction result was consistent with the previous study (Table III) (44).…”
Section: Genome-wide Identification Of Potential Phossnps In Hu-supporting
confidence: 82%
“…Also, it was proposed that a G1886S nsSNP of RYR2 (NM_001035) might generate a protein kinase C phosphorylation site (44). And our prediction result was consistent with the previous study (Table III) (44). Previously, Savas and Ozcelik (16) performed a small scale analysis to identify 15 nsSNPs that might create or remove potential phosphorylation sites in 14 DNA repair-and cell cycle-related proteins.…”
Section: Genome-wide Identification Of Potential Phossnps In Hu-supporting
confidence: 80%
“…This gene is responsible for release of calcium from the sarcoplasmic reticulum by the ryanodine receptor 2 (RyR2) [Shou et al 1998]. Arrhythmogenic right ventricular cardiomyopathy (ARVC) has also been reported in people with the RyR2 gene mutation [Milting et al 2006].…”
Section: Lim Domain Binding Protein 3 (Zasp/ldp3) and Lamin A/c (Lmna)mentioning
confidence: 99%
“…Single-channel recordings of CPVT-mutant RyR2 channels in planar lipid bilayers (37-39, 47, 99) revealed gain-of-function defects following PKA phosphorylation (47, 99) or caffeine stimulation (30, 40). Moreover, it has been demonstrated that CPVT-associated variants sensitize RyR2 to activation by cytosolic Ca 2+ (39, 99) and delay Ca 2+ -dependent channel inactivation (60). Alternative mechanisms for diastolic SR Ca 2+ leak through CPVT mutant RyR2 have been proposed and reviewed elsewhere (30, 37).…”
Section: The Ryanodine Receptor Macromolecular Complexmentioning
confidence: 99%